Case report: Anti-IgLON5 disease and anti-LGI1 encephalitis following COVID-19 - Li, Yanfei; Jia, Yanjie (Frontiers in Immunology, 2023)
Anti-IgLON family member 5 (IgLON5) disease is a rare autoimmune encephalitis, characterized by sleep problems, cognitive decline, gait abnormalities, and bulbar dysfunction. Anti–leucine-rich glioma-inactivated 1 (LGI1) autoimmune encephalitis is characterized by cognitive dysfunction, mental disorders, faciobrachial dystonic seizures (FBDS), and hyponatremia. Various studies report that coronavirus disease 2019 (COVID-19) have an effect on the nervous system and induce a wide range of neurological symptoms. Autoimmune encephalitis is one of the neurological complications in severe acute respiratory syndrome coronavirus 2 infection. Until now, autoimmune encephalitis with both anti-IgLON5 and anti-LGI1 receptor antibodies following COVID-19 is rarely reported. The case report described a 40-year-old man who presented with sleep behavior disorder, daytime sleepiness, paramnesia, cognitive decline, FBDS, and anxiety following COVID-19. Anti-IgLON5 and anti-LGI1 receptor antibodies were positive in serum, and anti-LGI1 receptor antibodies were positive in cerebrospinal fluid. The patient presented with typical symptoms of anti-IgLON5 disease such as sleep behavior disorder, obstructive sleep apnea, and daytime sleepiness. Moreover, he presented with FBDS, which is common in anti-LGI1 encephalitis. Therefore, the patient was diagnosed with anti-IgLON5 disease and anti-LGI1 autoimmune encephalitis. The patient turned better after high-dose steroid and mycophenolate mofetil therapy. The case serves to increase the awareness of rare autoimmune encephalitis after COVID-19.